Direct Detection of Thrombin Binding to 8-Bromodeoxyguanosine-Modified Aptamer: Effects of Modification on Affinity and Kinetics - Shou Goji; Jun Matsui (Journal of Nucleic Acids)
The affinity of an 8-bromodeoxyguanosine- (8-BrdG-) substituted thrombin-binding aptamer (TBA-Br), which has the 1st and 10th guanosine residues replaced with 8-BrdG, was estimated using reflectometric interference spectroscopy (RIfS). When comparing TBA-Br with unmodified TBA (TBA-H), it was demonstrated that the modification effectively improved the affinity of TBA; dissociation constants (KD) of TBA-H and TBA-Br were 45.4 nM and 1.99 nM, respectively. These values, which were obtained by direct observation of thrombin binding using RIfS, have the same order of magnitude as those obtained in our previous study utilizing conformational changes in TBA to detect thrombin binding, thus confirming the validity of the obtained KD values. RIfS measurements also revealed that the 8-BrdG modification resulted in a lower dissociation rate constant (kd), which suggests that the enhancement of affinity can be attributed to the stabilization of the G-quadruplex structure on introduction of 8-BrdG.